Phytosterols and their extraction from various plant matrices using supercritical carbon dioxide: a review - Uddin, Md. Salim; Sarker, Md. Zaidul Islam; Ferdosh, Sahena; Haque Akanda, Md. Jahurul Haque; Easmin, Mst. Sabina; Shamsudin, Siti Hadijah; Yunus, Kamaruzzaman (Elsevier Inc., 2015)
Phytosterols provide important health benefits: in particular, the lowering of cholesterol. From environmental and commercial points of view, the most appropriate technique has been searched for extracting phytosterols from plant matrices. As a green technology, supercritical fluid extraction (SFE) using carbon dioxide (CO2) is widely used to extract bioactive compounds from different plant matrices. Several studies have been performed to extract phytosterols using supercritical CO2 (SC-CO2) and this technology has clearly offered potential advantages over conventional extraction methods. However, the efficiency of SFE technology fully relies on the processing parameters, chemistry of interest compounds, nature of the plant matrices and expertise of handling. This review covers SFE technology with particular reference to phytosterol extraction using SC-CO2. Moreover, the chemistry of phytosterols, properties of supercritical fluids (SFs) and the applied experimental designs have been discussed for better understanding of phytosterol solubility in SC-CO2. (c) 2014 Society of Chemical Industry